Rancang Bangun Aplikasi Pengelolaan Dokumen Sistem Penjaminan Mutu Internal Berbasis Web di Stikom Surabaya - Ubaidillah, Prayugi; Tjandrarini, A.B; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Quality Assurance and Supervision Center (Pusat Pengawasan dan Penjaminan Mutu-P3M) is a work unit which preparing, controlling, evaluating, and developing Internal Quality Assurance System (Sistem Penjaminan Mutu Internal-SPMI). At the moment P3M experiencing some problems regarding documents management. That is because in managing document such as organizing, numbering, ratification, publishing, revisioning, and extermination are still done manually. It wasted time, documents building up, and document distribution process is delayed because there is a different schedule to coordinating with related workers.Based on that problem, therfore the solution that can be offered is designing and building an application which can help to manage SPMI documents. With this application, eventhough the interested party with particular document are absent, the interested party still can access the document online because this application is web based.The results of the trial showed that this application can provide convenience in the management process that is at the stage of drafting, document search, validation, publishing, revision and evaluation, as well as the distribution of documents to every unit.Quality Assurance and Supervision Center (Pusat Pengawasan dan Penjaminan Mutu-P3M) is a work unit which preparing, controlling, evaluating, and developing Internal Quality Assurance System (Sistem Penjaminan Mutu Internal-SPMI). At the moment P3M experiencing some problems regarding documents management. That is because in managing document such as organizing, numbering, ratification, publishing, revisioning, and extermination are still done manually. It wasted time, documents building up, and document distribution process is delayed because there is a different schedule to coordinating with related workers.Based on that problem, therfore the solution that can be offered is designing and building an application which can help to manage SPMI documents. With this application, eventhough the interested party with particular document are absent, the interested party still can access the document online because this application is web based.The results of the trial showed that this application can provide convenience in the management process that is at the stage of drafting, document search, validation, publishing, revision and evaluation, as well as the distribution of documents to every unit.